The Experimental TASK-1 Potassium Channel Inhibitor A293 Can Be Employed for Rhythm Control of Persistent Atrial Fibrillation in a Translational Large Animal Model - Wiedmann, Felix; Beyersdorf, Christoph; Zhou, Xiao-Bo; Kraft, Manuel; Foerster, Kathrin I.; El-Battrawy, Ibrahim; Lang, Siegfried; Borggrefe, Martin; Haefeli, Walter E.; Frey, Norbert; Schmidt, Constanze (Frontiers in Physiology, 2021)
Abstract Background: Upregulation of the two-pore-domain potassium channel TASK 1 (hK2P3.1) was recently described in patients suffering from atrial fibrillation (AF) and resulted in shortening of the atrial action potential. In the human heart, TASK 1 channels facilitate repolarization and are specifically expressed in the atria. In the present study, we tested the antiarrhythmic effects of the experimental ion channel inhibitor A293 that is highly affine for TASK 1 in a porcine large animal model of persistent AF. Methods: Persistent AF was induced in German landrace pigs by right atrial burst stimulation via implanted pacemakers using a biofeedback algorithm over 14 d. Electrophysiological and echocardiographic investigations were performed before and after the pharmacological treatment period. A293 was intravenously administered once per day. After a treatment period of 14 d, atrial cardiomyocytes were isolated for patch clamp measurements of currents and atrial action potentials. Hemodynamic consequences of TASK-1 inhibition were measured upon acute A293 treatment. Results: In animals with persistent AF, the A293 treatment significantly reduced the AF burden (6.5 % vs. 95 %; P < 0.001). Intracardiac electrophysiological investigations showed that the atrial effective refractory period was prolonged in A293 treated study animals, whereas, the QRS width, QT interval, and ventricular effective refractory periods remained unchanged. A293 treatment reduced the upregulation of the TASK 1 current as well as the shortening of the action potential duration caused by AF. No central nervous side effects were observed. A mild but significant increase in pulmonary artery pressure was observed upon acute TASK-1 inhibition. Conclusion: Pharmacological inhibition of atrial TASK 1 currents exerts in vivo antiarrhythmic effects that can be employed for rhythm control in a porcine model of persistent AF. Care has to be taken as TASK-1 inhibition may increase pulmonary artery pressure levels.